1997
DOI: 10.1080/13577149778425
|View full text |Cite
|
Sign up to set email alerts
|

Should Cancer Survivors Fear Radiation‐Induced Sarcomas?

Abstract: A bstractPurpose/Results. Ionizing radiation is carcinogenic and the induction of a second malignancy is a serious potential long-term complication of radiotherapy. The incidence of radiation-induced sarcomas was evaluated from many large epidemiological surveys of long-term cancer survivors reported in the literature over the past 30 years and only one case was found for every 1000 patients irradiated. D iscussion. Although greater numbers of cancer patients are receiving radical radiotherapy and surviving fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…[5] found that relative risk for bone sarcoma in the irradiated field was 3.0. The overall incidence of post-irradiation sarcoma ranged from 0.03% after 10 years to 0.8% after 30 years [15, 17–19]. …”
Section: Discussionmentioning
confidence: 99%
“…[5] found that relative risk for bone sarcoma in the irradiated field was 3.0. The overall incidence of post-irradiation sarcoma ranged from 0.03% after 10 years to 0.8% after 30 years [15, 17–19]. …”
Section: Discussionmentioning
confidence: 99%
“…The most common acute adverse events associated with radiotherapy include erythema and desquamation 2 . Although the presence of telangiectasias and hypopigmentation account for the majority of late side effects, there is a low risk of radiation‐induced malignancy that can occur years after the initial exposure 5 . Moreover, the risk of radiation‐induced malignancy would be substantially lower than the risk of death resulting from the general anesthesia administered during resection and reconstruction of an advanced basal cell carcinoma.…”
Section: Relative Indications For Radiotherapy In Basal Cell Carcinomamentioning
confidence: 99%
“…2 Although the presence of telangiectasias and hypopigmentation account for the majority of late side effects, there is a low risk of radiation-induced malignancy that can occur years after the initial exposure. 5 Moreover, the risk of radiation-induced malignancy would be substantially lower than the risk of death resulting from the general anesthesia administered during resection and reconstruction of an advanced basal cell carcinoma. The true 5-year recurrence rate after radiotherapy for basal cell carcinoma is difficult to determine as many studies do not distinguish between histologic subtypes and initial tumor size.…”
mentioning
confidence: 99%
“…A rise of radiationinduced malignancies is an infrequent (about 0.03%) [17] but well-recognized outcome after radiation treatment [21,26,27,30] and has been described for atomic bomb survivors [25] and Chernobyl survivors [23]. At most, 5% of all second primary cancers can be convincingly linked to the radiation treatment and about 0.1% of radiotherapy patients developed sarcomas (reviewed in [7]). Occurrence of radiation-induced sarcomas is reported relatively often in the literature [10,27] (reviewed in [16]).…”
mentioning
confidence: 98%